Implementation of Integrated People-Centered Eye Care at Sub-District Level in Barru - Rakatama, Rahmat Priyangga; Amalius, Ahmad Ashraf; Faisal, Andi Akhmad; Kamaruddin, Muhammad Irfan (Majalah Oftalmologi Indonesia, 2023)
Purpose: Integrated People-Centered Eye Care (IPCEC) was initiated by the World Health Organization as a global strategy in community-centred and integrated health services. In Indonesia, the Rapid Assessment of Avoidable Blindness survey showed the largest number of moderate and severe visual impairment was found in South Sulawesi, particularly uncorrected refractive error (33.8%). The results of this study are expected to initiate and introduce IPCEC-based eye health services and promotion at the sub-district level. Methods: The program started with advocacy of eye health programs at the sub-district level to policy makers. In schools, education and training for visual acuity examination were given to teachers. All children who failed the screening or have ocular abnormalities are referred to eye care center. Mass counseling and examination were also carried out at the health center simultaneously with screening for mass cataract surgery at the Barru District Hospital. Results: Implementation of IPCEC was welcomed by Barru District government. School eye health program conducted by the teachers in 5 schools screened 1263 students with 90.74% of the students had normal visual acuity. Mass screening at the Pekkae and Pancana Public Health Centers found that most participants had cataracts (58%) followed by refractive error (38%). Conclusion: Visual acuity examination among school-age children by the teacher will improve early detection of refractive errors. Screening by eye health worker at public health center needs to be carried out to identify blindness causes often found in the community, and proceed with prescribing drugs, eyeglasses, and mass cataract surgery as definitive step in eradicating blindness.